Processamento convencional e assistido por campo elétrico (Flash Sintering) de cerâmicas livres de chumbo baseadas em K0,5Na0,5NbO3: propriedades físicas finais - Zapata, Angélica Maria Mazuera (2020)
K0,5Na0,5NbO3 (KNN)-based ceramics are considered promising candidates to replace lead-based piezoelectric ceramics, such as Pb(ZrxTi1−x)O3, which are widely used in electro electronic devices. However, obtaining KNN-based ceramics without secondary phases, abnormal grain growth, or problems with partial volatilization of alkali elements represents the main challenge. Therefore, in this work, a study was proposed to optimize the processing conditions of KNN-based ceramics with composition Li0,04(K0,5Na0,5)0,96Nb0,8Ta0,2O3 (LKNNT), both by the conventional sintering as well as by flash sintering method (AC and DC modes). Into synthesis of LKNNT was identified the K3Li2Nb5O15 composition (KLN) as a secondary phase, which causes porosity and low densification (90,8%). However, alternatives as to the addition of 2 wt% excess Li, increasing of the mixing and milling times (24 h), and the use of starting orthorhombic phase Nb2O5, allowed to obtain ceramics without secondary phase, and high densification (97,5%). The synchrotron light measurements in LNLS as a function of temperature showed a morphotropic phase boundary between the orthorhombic and tetragonal phases at room temperature, with a proportion of 19% and 81%, respectively. An anomaly observed at 450 °C in the dielectric permittivity measurements was related to the KNN core-shell microstructures, produced by partial volatilization processes of the alkali elements, compositional inhomogeneity, and the presence of secondary phases. On the other hand, the mechanical and dielectric measurements showed the orthorhombic to tetragonal (TO−T) and the tetragonal to cubic (TT −C) phase transition temperatures around 100 °C and 325 °C for LKNNT, respectively. Flash sintering experiments were performed with the pellet-shaped specimens at 250 - 512 V/cm of electric field and maximum current density of 3 - 20 mA/mm2. The flash event for both KNN and LKNNT was attained around 870 °C. The Partial volatilization processes of alkali elements were observed in the DC mode, followed by the formation of K6Nb10,88O30 and KLN secondary phases. The secondary phases were produced mainly during the sintering process by the reduction and volatilization of Na, causing low densification in the material. Hence, the use of a DC electric field facilitates the formation of the secondary phase in the positive electrode (anode), and a sodium electrochemical reduction in the negative electrode (cathode). However, the use of an AC electric field allowed to obtain KNN at 870 °C for 90 s, without the presence of any secondary phase and with high relative density (94,5%). In the case of LKNNT, a hard electrochemical reaction between the sample and the platinum electrodes led to the breaking of electrical conductivity and low densification. Therefore, were suggested electrochemical processes between the sample and the platinum electrodes during the sintering process to explain the growth of Na2Pt and Li2Pt layers at 900 °C. This reaction causes the formation of an isolated region into the sample-electrode interface, breaking of the electrical conductivity.